KOORDINASI RELE DIFFERENSIAL 87GT DAN RELE ARUS LEBIH 51/27 DI GENERATOR-TRANSFORMATOR TERHADAP GANGGUAN HUBUNG SINGKAT UNIT 3 PLTP GUNUNG SALAK - Budi Santosa; Muchamad Nur Qosim; Hendrianto Husada (Sutet, 2015)
The power plant has several components one of which is the Generator and Transformer which become the vital equipment in a power plant. Therefore from the reliability and sustainability of a generator and transformer is very dependent on the protection system used. In this studi discusses the adjustment of differential releases and more currents and coordination of both in the event of interference obtained from the data processing. The value of the adjusting current in the differential releases of 1.75 A with 0.2% mismatch and 6.3 A more current releases and the coordination between the differential releases and the overcurrent is limited by the delay time set on the overcurrent current with the TMS value of 0.159 and The greater the noise current the faster the working time of the relay provides a trip signal to the circuit breaker.